Regional autonomy and social development some notes on the case of Muslim Mindanao - Tanggol, Sukarno D. (Philippine Journal of Public Administration, 1990)
Amidst the raging controversy on the Mindanao problem, genuine autonomy seems to be the only acceptable alternative to its resolution beyond secession and war. But autonomy must move far beyond the decorative nature of PD 1618 and substantial governmental powers and functions must be devolved from the national government to the regional autonomous government. Autonomy implies a change to a pluralist approach for national integration and may unite and preserve the 'wholeness of Philippine society in its ethnolinguistic, cultural, and even religious diversities.*Autonomy may also be consistent with the goals of equity and social justice as the Muslim community's diminishing access to political power and economic resources may be restored. Finally, autonomy may actualize the ideals of a government that is closer to the people where goods and services are not only delivered efficiently and effectively but more importantly, according to the real demands and needs of the client communities.